2015
DOI: 10.1080/09658211.2015.1018277
|View full text |Cite
|
Sign up to set email alerts
|

Visual object imagery and autobiographical memory: Object Imagers are better at remembering their personal past

Abstract: In the present study we examined whether higher levels of object imagery, a stable characteristic that reflects the ability and preference in generating pictorial mental images of objects, facilitate involuntary and voluntary retrieval of autobiographical memories (ABMs). Individuals with high (High-OI) and low (Low-OI) levels of object imagery were asked to perform an involuntary and a voluntary ABM task in the laboratory. Results showed that High-OI participants generated more involuntary and voluntary ABMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 67 publications
7
48
1
Order By: Relevance
“…Indeed, it has been widely suggested that autobiographical memories are dominated by visual imagery and that the retrieval of visual images is the core feature of autobiographical reliving (Brewer, 1996; Conway, 2009). In line with this idea, a study has shown poor autobiographical recall in healthy young participants with low ability to generate pictorial mental images of objects (Vannucci, Pelagatti, Chiorri, & Mazzoni, 2015). Neuropsychological studies have also shown that lesions resulting in a loss of the ability to generate visual images also result in retrograde amnesia (Brown & Chobor, 1995; Greenberg, Eacott, Brechin, & Rubin, 2005; Ogden, 1993).…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, it has been widely suggested that autobiographical memories are dominated by visual imagery and that the retrieval of visual images is the core feature of autobiographical reliving (Brewer, 1996; Conway, 2009). In line with this idea, a study has shown poor autobiographical recall in healthy young participants with low ability to generate pictorial mental images of objects (Vannucci, Pelagatti, Chiorri, & Mazzoni, 2015). Neuropsychological studies have also shown that lesions resulting in a loss of the ability to generate visual images also result in retrograde amnesia (Brown & Chobor, 1995; Greenberg, Eacott, Brechin, & Rubin, 2005; Ogden, 1993).…”
Section: Discussionmentioning
confidence: 86%
“…Participants in the voluntary condition were shown a subset of the same cue phrases and had to retrieve a memory to each one. This laboratory method confirmed the difference in specificity found in diary studies (Cole et al ., ; Schlagman & Kvavilashvili, ; Vannucci, Pelagatti, Chiorri, & Mazzoni, ).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies demonstrated that vivid and pictorial object imagery may facilitate memory (Marks, 1973;Vannucci, Pelagatti, Chiorri, & Mazzoni, 2016), other literature showed that the elaboration of sensory details during the encoding leads to the increase in source memory errors (Thomas, Bulevich, & Loftus, 2003). Research has suggested that vivid and rich in sensory detail imagery experiences may lead to later confusion between real and imagined experiences, causing false memory errors (Gonsalves & Paller, 2000;Gonsalves et al, 2004).…”
Section: Introductionmentioning
confidence: 99%